Peranan Anggota DPRD Sumatera Utara Fraksi Golongan Karya (Golkar) Dalam Mengupayakan Aspirasi Masyarakat - Khairil Ihsan; Tengku Khofifah Khairunisa; Ibnu Zulkhoir; Ahmad Nasir Hasibuan; Fitriani Fitriani (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
One of the duties and functions of DPRD members, namely members of the district DPRD, includes the obligation to absorb and collect constituent aspirations through regular working visits, accommodate and follow up on public aspirations and complaints, and provide moral and political accountability to constituents in their constituency. The research used in this study is a qualitative approach. As for what is meant by qualitative research, namely research that intends to understand the phenomenon of what is experienced by research subjects holistically, and by means of descriptions in the form of words and language, in a special natural context and by utilizing various scientific methods. This research resulted that the members of the North Sumatra DPRD members of the Golongan Karya faction in fighting for the aspirations of the people were carried out by members of the parliament as the people's representatives in the legislature using several methods. The role of DPRD members is to oversee the running of government and to be a connector of people's aspirations for the government. The role of DPRD members in fighting for people's aspirations has been carried out optimally. Keywords: DPRD, Recess, Community Aspirations